Application of Calcium Aluminate Doped with Mn and Cr in Optical Thermometry - Rogulis, Uldis; Fedotovs, Andris; Rodionovs, Pavels; Kemere, Meldra; Antuzevics, Andris; Sarakovskis, Anatolijs; Alps, K.; Kiseleva, V. (Sciendo, 2023)
Optical thermometers are advantageous for temperature measurement in electromagnetic fields and aggressive environments; however, their composition mostly relies on materials doped with expensive and resource-limited rare earth ions. In this article, we describe the application of calcium aluminate doped with transition metal ions (Mn2+ and Cr3+) in optical thermometry, employing optical fibres for signal transmission. Upon excitation with 450 nm laser diode radiation, changes in the luminescence of Mn2+ ions in the 500–550 nm band are followed along with changes in the Cr3+ band at 750–800 nm. The application has been tested in the temperature range from 20 °C to 800 °C. The temperature dependence of Cr3+ luminescence encompasses the high-temperature range, whereas the luminescence band of Mn2+ ions gives an increase in the total intensity and provides a more consistent change in the range from 400 °C to 550 °C. --//-- This is an open access article Rogulis, U., Fedotovs, A., Rodionovs, P., Kemere, M., Antuzevics, A., Sarakovskis, A., Alps, K. and Kiseleva, V.. "Application of Calcium Aluminate Doped with Mn and Cr in Optical Thermometry" Latvian Journal of Physics and Technical Sciences, vol.60, no.5, 2023, pp.15-21. https://doi.org/10.2478/lpts-2023-0027 published under the CC BY-NC-ND 4.0 licence.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; Calcium aluminate; electron paramagnetic resonance (EPR); Mn2+ and Cr3+ ions; luminescence; optical thermometry